Using Resistivity Measurements to Determine Anisotropy in Soil and Weathered Rock - Soto-Caban, S.; Law, E. (Engineering, Technology & Applied Science Research, 2013)
This study uses electrical resistivity measurements of soils and weathered rock to perform a fast and reliable evaluation of field anisotropy. Two test sites at New Concord, Ohio were used for the study. These sites are characterized by different landform and slightly east dipping limestone and siltstone formations of Pennsylvanian age. The measured resistivity ranged from 19 Ω∙m to 100 Ω∙m, and varied with depth, landform, and season. The anisotropy was determined by a comparison of resistance values along the directions of strike and the dip. Measurements showed that the orientation of electrical anisotropy in the shallow ground may vary due to fluid connection, which is determined by the pore geometry in soil and rock, as well as by the direction of fluid movement. Results from this study indicated that a portable electrical resistivity meter is sensitive and reliable enough to be used for shallow ground fluid monitoring.